The Role of Time Management on Behavior and Perception with Qualitative Descriptive - Suci Pertiwi; Sophya Hadini Marpaung; Joosten Joosten (Jurnal Varian, 2023)
Problems that occur at Mikroskil University student organizations include obstacles from the administrative side, such as delays in submitting proposals and reporting activities which result in delays/especially delays in the funding process, to issues of morality and management of each student organization as well as time management itself. This research aims to determine and analyze the condition of Mikroskil University student organizations in running student organizations so that student perceptions and behavior can be known, and this is the novelty of this research. This research used a qualitative descriptive survey method with a purposive sampling technique involving core administrators and active members of divisions within Mikroskil University as samples. The results of the partial test (t-test) show that the time management variable has a positive effect on student behavior and perceptions at the Mikroskil University Student Organization. The Adjusted R2 value of the time management variable on student behavior was obtained at 44.8%, while the time management variable on behavior towards student perceptions was 32.8% and the remaining 55.2% and 67.2% were influenced by other variables not examined in this research. The research results show that time management partially has a positive and significant effect on behavior and perceptions